The effect of time and environmental conditions on Touch DNA. Issue 1 (December 2019) - Alketbi, Salem K.; Goodwin, W.
Abstract: Touch DNA analysis has become an important aspect of a forensic laboratory's workload and a crucial tool for investigators in many cases. However, there is a lack of research regarding the influence of environmental conditions on Touch DNA, which is proven to reduce traces of biological material in samples. This study investigated the influence of time between deposition and recovery of Touch DNA, as well as the impact of temperature and humidity on a range of porous and non-porous surfaces.